Co-production of Cellulases and Manganese Peroxidases by Bacillus sp. R2 and Bacillus Cereus 11778 on Waste Newspaper: Application in Dyes Decolourization. (2015) - Khelil, Omar; Choubane, Slimane; Cheba, Ben Amar
Abstract: In the current study two different strains of Bacillus ( Bacillus sp. R2 and Bacillus cereus 11778) were used in single and mixed culture to study the co-production of cellulases and manganese peroxidases using waste newspaper as a sole carbon source. The highest level of cellulases production was noticed after 24 h in the mixed culture (1.08 ± 0.02 FPU mg-1). While the lowest production was observed also in the mixed culture after 72 h of incubation (0.47 ± 0.03 FPU mg-1). For the peroxidases production we noticed that Bacillus sp. R2 and the mixed culture have shown an important capacity to produce peroxidases. A strong positive correlation between cellulase and Mn peroxidase was detected in Bacillus sp. R2, In Bacillus cereus there was no correlation detected, while in the mixed culture we noticed that cellulase has a strong negative correlation with Mn peroxidase. The obtained results showed a remarkable dyes decolorization. Concerning Methylene blue the highest level of decolourization was noticed in Bacillus cereus (47%). For neutral red the degree of decolourization was around 80% and that for all cultures. Finally, for Congo red decolourization has reached his maximum level after only 135 min of reaction for the three cultures (69%, 69% 72% respectively).